2020
DOI: 10.1080/2162402x.2020.1794423
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the gut microbiota composition and the bioactivity of immunostimulatory commensals for the optimization of immune checkpoint inhibitors

Abstract: Accumulating evidence from preclinical studies and human trials demonstrated the crucial role of the gut microbiota in determining the effectiveness of anticancer therapeutics such as immunogenic chemotherapy or immune checkpoint blockade. In summary, it appears that a diverse intestinal microbiota supports therapeutic anticancer responses, while a dysbiotic microbiota composition that lacks immunostimulatory bacteria or contains overabundant immunosuppressive species causes treatment failure. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
(170 reference statements)
0
7
0
Order By: Relevance
“…The microbiome is a hot topic in the healthcare industry. The microbiome has strong effects on obesity 23 , immunity 24 , vaccine efficacy 25 , and immune checkpoint inhibitors in cancer 26 . Many probiotics and prebiotics have been developed and are under development; however, the regulation of the sensing mechanisms is not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome is a hot topic in the healthcare industry. The microbiome has strong effects on obesity 23 , immunity 24 , vaccine efficacy 25 , and immune checkpoint inhibitors in cancer 26 . Many probiotics and prebiotics have been developed and are under development; however, the regulation of the sensing mechanisms is not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of the gut microbiome determines the effect of anticancer therapy including immunogenic chemotherapy and immune checkpoint blocker [48]. Tumorigenesis is sometimes combined with immunosuppression which decreases the anticancer immunological defense activated in the host [49].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…They have as well discussed preclinical and clinical investigations that have enhanced our understanding about the roles and the mechanisms through which microbiome influences the response to treatment with immune checkpoint inhibitors [51]. It seems that a variable gut microbiota supports therapeutic anticancer responses, while a microbiome composition that lacks immunostimulatory bacteria or contains excessive immunosuppressive species results in treatment failure [48]. T cell immunoglobulin together with mucin domain-containing protein-3 (Tim-3) are immune checkpoint molecules and targets for anti-cancer therapy [52].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…The gut microbiota also plays a role in anticancer responses: a dysbiotic microbiota composition lacking immunostimulatory bacteria or containing immunosuppressive species causes treatment failure [41]. The gut microbiome was recently recognized to influence the effectiveness of PD-1-based anticancer immunotherapy, and the authors concluded that healthy gut flora is a determinant of the anticancer response [42].…”
Section: Liver Cancer Pathogenesis and Immunological Tolerance As The Basis For Hcc Developmentmentioning
confidence: 99%